2005
DOI: 10.1111/j.1754-4505.2005.tb01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home executive directors' perception of oral care in long-term care facilities.

Abstract: Oral health in long-term care (LTC) facilities has been repeatedly documented as less than ideal. The complex nature of this environment has made it difficult to understand and improve the oral health status of residents through education and training. The purpose of the study was to investigate how the executive directors (EDs) of LTC facilities value oral health and to determine facility variables, which may influence how oral care is delivered. A mail survey of the EDs of all LTC facilities in Ohio (n = 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…Johnson and Lange 37 reported that 40% of home directors questioned were satisfied with the dental care provided. Pyle et al 38 reported that 63.4% of home directors were satisfied with the dental care in their facilities, although 49% of home directors rated the oral health of their residents as moderate to poor. These studies highlight the lack of awareness of dental problems amongst home directors.…”
Section: Discussionmentioning
confidence: 98%
“…Johnson and Lange 37 reported that 40% of home directors questioned were satisfied with the dental care provided. Pyle et al 38 reported that 63.4% of home directors were satisfied with the dental care in their facilities, although 49% of home directors rated the oral health of their residents as moderate to poor. These studies highlight the lack of awareness of dental problems amongst home directors.…”
Section: Discussionmentioning
confidence: 98%
“…In some guidelines, such as British Thoracic Society guidance on the prevention of CAP, oral hygiene is not mentioned (Lim 2009 ). Moreover, nurses have limited knowledge regarding provision of mouth care in general (Frenkel 2000;Jablonski 2005;Pyle 2005). Chiba 2009 reported that 32.4% of caregivers hesitated to provide oral care measures, which indicated their lack of knowledge about oral hygiene but bespoke oral health education has been shown to have a positive effect on caregivers' knowledge and attitudes (Charteris 2001;Frenkel 2001;.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…In earlier research, behavior meeting this definition was usually labeled as “uncooperative behavior” (Adams, 1996; Kambhu & Levy, 1993; Pyle, Jasinevicius, Sawyer, & Madsen, 2005), “disruptive behavior” (Algase et al, 1996; Kolanowski & Whall, 2000; Whall, 2002), or as “agitation” (Volicer, Bass, & Luther, 2007). Investigators in the past decade have made important distinctions between the latter construct and resistiveness to care.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%